A strategy for the management of hospitalized children with acute lower respiratory infections - Ferrari, Ana M; Pirez, María C; Ferreira, Alicia; Rubio, Ivonne; Montano, Alicia; Lojo, Rosa; Palomino, Graciela; Giachetto, Gustavo; Galiana, Alvaro; Sarachaga, María J; Mercado, Silvana; Martinez, Osvaldo; et al. (Revista de Saúde Pública, 2002)
OBJECTIVES: To improve the quality of care provided to hospitalized children having acute lower respiratory infections (ALRI), to increase the knowledge on this health condition, and to broaden the utilization of health care resources through a program called "Winter Plan". METHODS: The program comprised the use of guidelines for diagnosis and treatment, disease-oriented hospitalizations to provide an increased level of care, management of health care resources and implementation of computerized medical records. Systematic investigation of viral etiology was performed in order to rationalize the use of medications and reduce nosocomial infections. RESULTS: During program implementation (19/V-19/IX/99), 3,317 children were admitted; 1,347 (40.61%) had ALRI, of which 1,096 (81%) were included in the study. Of them, 71% aged less than 1 year. Most ALRI were viral (68%). Admission criteria were: oxygen saturation